Teledermatology in Nepal: Where are we? - S Saraswoti Neupane (Nepal Journal of Dermatology, Venereology & Leprology)
Teledermatology is the practice of clinical dermatology by making use. of images , computers and telecommunication technologies for the diagnosis and treatment ·of skin conditions. The technology involves two different approaches, store-and-forward approach and real-time interaction. Although it has a long history, its implementation in Nepal is still in the period of conception. Both the approaches have their own advantages, but they are not. free from disadvantages. In Nepal, rapidly growing telecommunication facility throughout the country can be utilized to increase the accessibility to dermatology consultation service. Considering the high burden of skin diseases compared to the limited number of dermatologists in the country, teledermatology could be an effective tool in improvement of the health care delivery system.